(untitled) (Economia Aplicada, 1998)
This paper analyzes Brazil's recent experience with an exchange rate based stabilization program, the Piano Real, its development and future possibilities. The feature of using the exchange rate as an anchor in a disinflation program and the role ofits credibility and its interaction with expectations regarding the sustainability and political feasibility of government stabilization policies are examined. Finally, the problems that have arisen while establishing new institutional arrangements, such as a new currency or a policy rule for monetary base creation, and the evolution ofthe main economic indicators, during and after the implementation ofthe program, are briefly discussed in an attemptto draw from this stabilization experiment lessons for the future. The effects ofthe Mexican crisis of December 1994 upon the performance ofthe Brazilian economy are also emphasized.